2019
DOI: 10.1186/s12942-019-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

Urban and rural differences in geographical accessibility to inpatient palliative and end-of-life (PEoLC) facilities and place of death: a national population-based study in England, UK

Abstract: Background Little is known about the role of geographic access to inpatient palliative and end of life care (PEoLC) facilities in place of death and how geographic access varies by settlement (urban and rural). This study aims to fill this evidence gap. Methods Individual-level death data in 2014 (N = 430,467, aged 25 +) were extracted from the Office for National Statistics (ONS) death registry and linked to the ONS postcode directory file to derive settlement of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 53 publications
1
39
1
Order By: Relevance
“…Existing studies have used national level estimates, which can mask nuances in regional level geographic access. For example, in a previous national population-based study we found rural-urban variations in geographic access to hospices, with urban dwellers having better access to inpatient hospice facilities compared to their rural counterparts [19]. Our findings were, however, limited in the extent to which they may be generalisable to regions within England, UK.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Existing studies have used national level estimates, which can mask nuances in regional level geographic access. For example, in a previous national population-based study we found rural-urban variations in geographic access to hospices, with urban dwellers having better access to inpatient hospice facilities compared to their rural counterparts [19]. Our findings were, however, limited in the extent to which they may be generalisable to regions within England, UK.…”
Section: Introductioncontrasting
confidence: 65%
“…Geographic access was the explanatory variable analysed in categories (0-10 minutes, 10-30 minutes, 30-50 minutes and Over 50 minutes). We analysed access as categorical variable to facilitate easy comparison across regions and to compare findings with previous study [19]. Geographic access was measured by calculating drive times from patients' place of residence to nearest hospices taking into account the speed limits of various road types.…”
Section: Variable Definitionsmentioning
confidence: 99%
“…Despite the increasing use of geographical information systems and spatial analyses to better understand health care access in developing countries, there are still important gaps in its application. Studies in high income countries provide accurate estimates of geographical access to services due to the wider availability of electronic health information systems and GIS data, as well as good transport infrastructure [63,[67][68][69][70]. In contrast, studies in developing countries typically use either Euclidean distances to obtain a basic measure of distance, or road networks in combination with friction surfaces to obtain estimates of travel time to PHC because the real network of footpaths is rarely available [21,27,41].…”
Section: Discussionmentioning
confidence: 99%
“…Most Norwegian cancer patients (around 65%) die in their communities, either at home (10-15%) or in nursing homes (around 50%) [52]. A population-based study from England, UK, showed that patients living in rural areas had worse geographic access to hospitals than patients living in urban areas and were more likely to die at home [53]. Norway is a sparsely populated country, and many Norwegians have long travel distances to hospitals and to palliative care units.…”
Section: Discussionmentioning
confidence: 99%